2012
DOI: 10.3389/fnhum.2012.00046
|View full text |Cite
|
Sign up to set email alerts
|

Non-Pharmacological Intervention for Memory Decline

Abstract: Non-pharmacological intervention of memory difficulties in healthy older adults, as well as those with brain damage and neurodegenerative disorders, has gained much attention in recent years. The two main reasons that explain this growing interest in memory rehabilitation are the limited efficacy of current drug therapies and the plasticity of the human central nervous and the discovery that during aging, the connections in the brain are not fixed but retain the capacity to change with learning. Moreover, seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 190 publications
1
53
1
4
Order By: Relevance
“…We reviewed and summarized the primary research articles from each of the eight previous reviews and meta-analytic studies noted above (Belleville, 2008;Cotelli et al, 2012;Huckans et al, 2013;Li et al, 2011;Reijnders et al, 2013;Simon et al, 2012;Stott & Spector, 2011). This resulted in 29 studies, 1 of which was excluded because it was written in Chinese (Chen et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We reviewed and summarized the primary research articles from each of the eight previous reviews and meta-analytic studies noted above (Belleville, 2008;Cotelli et al, 2012;Huckans et al, 2013;Li et al, 2011;Reijnders et al, 2013;Simon et al, 2012;Stott & Spector, 2011). This resulted in 29 studies, 1 of which was excluded because it was written in Chinese (Chen et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…It is important to note that these conclusions rested on only three studies that used a wide variety of techniques. Over the past 3 years, there have been at least seven reviews (Belleville, 2008;Cotelli, Menenti, Zanetti, & Miniussi, 2012;Huckans et al, 2013;Jean, Bergeron, Thivierge, & Simard, 2010;Reijnders, van Heugten, & van Boxtel, 2013;Simon, Yokomizo, & Bottino, 2012;Stott & Spector, 2011) and one meta-analysis (Li et al, 2011) that examined whether the cognitive rehabilitation of memory can be effective in those with MCI. The results of all eight of these works generally indicated that patients could benefit from memory rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…In rTMS, several successive pulses are applied rhythmically in the same sequence, and allow the modulation of cortical excitability (Rossi et al, 2009). A frequency is considered to have a low stimulation when it is equal to or above one pulse per second (1 Hz), which fosters inhibitory activity, and to have a high stimulation when it is between 5 Hz and 20 Hz, which causes an increase in cortical excitability (Cotelli, Manenti, Zanetti, & Miniussi, 2012;Higgins, 2008;Hsu, Ku, Zanto & Gazzaley, 2015;Manenti, Cotelli, Robertson & Miniussi, 2012;Nardone et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As life expectancy continues to increase, the number of older people unable to live independently and in need of assistance because of age-related cognitive impairments is rapidly rising worldwide (Cotelli, Manenti, Zanetti, & Miniussi, 2012;Grady & Craik, 2000;.…”
Section: Population and Agingmentioning
confidence: 99%
“…Memory declines with psychological aging and causes people to experience memory problems (Cotelli et al, 2012;Schmitter-Edgecombe & Woo, 2009 Kwok et al, 2013). Dementia is a progressive degenerative brain syndrome that involves memory impairment in older adults caused by damage to brain cells and their connections.…”
Section: The Impact Of Cognitive Impairment In the Older Populationmentioning
confidence: 99%